The anti‐adipogenic effect of peripheral blood mononuclear cells is absent with PCSK9 loss‐of‐function variants. Issue 11 (24th September 2016) - Gagnon, AnneMarie; Ooi, Teik C.; Cousins, Marion; Favreau, Colette; Henry, Kathy; Landry, Anne; Sorisky, Alexander
Abstract : Objective: To determine the effect of (1) an oral fat load and (2) pro‐protein convertase subtilisin/kexin type (PCSK) 9 loss‐of‐function (LOF) variant status on the ability of peripheral blood mononuclear cells (PBMC) to inhibit human adipogenesis. Methods: PBMC from subjects with one or more PCSK9 LOF variants versus non‐variant controls were compared in the fasting state and after an oral fat load. Results: Fasting triglyceride (TG) levels were lower in the LOF variant versus non‐variant group but rose to the same level after the oral fat load. Conditioned medium from PBMC was obtained in fasting (PBMC‐CM‐F) and 4‐h postprandial (PBMC‐CM‐PP) states. PBMC‐CM‐PP from non‐variant controls inhibited adipogenesis of human preadipocytes more than did PBMC‐CM‐F. In contrast, PBMC‐CM‐F or ‐PP from PCSK9 LOF variant subjects had no effect on adipogenesis. After the oral fat load, PBMC from PCSK9 LOF variant subjects showed significant increases in mRNA levels of interleukin‐1β, tumor necrosis factor‐α, sterol regulatory element binding protein‐1c, CD36, and monocyte chemoattractant protein‐1 (MCP‐1), only MCP‐1 mRNA levels increased in PBMC from non‐variant controls. Conclusions: The absence of anti‐adipogenic action of PBMC from PCSK9 LOF variant subjects points to a novel role for PCSK9 in PBMC‐adipose cell interactions.